Impact of Pb on Chlamydomonas reinhardtii at Physiological and Transcriptional Levels - Zheng, Canqi; Aslam, Muhammad; Liu, Xiaojuan; Du, Hong; Xie, Xihui; Jia, Haojie; Huang, Nan; Tang, Kaiming; Yang, Yingquan; Li, Ping (Frontiers in Microbiology, 2020)
Trace elements stress is one of the most damaging abiotic stresses in environment. Nevertheless, the defense mechanism in microalgae remains poorly understood. In this study, physiological and molecular methods were performed to analyze the defense responses in green alga Chlamydomonas reinhardtii. It was speculated that the defense responses might mainly be due to the regulation of hormone signaling, indicating its potential role in alleviating the Pb toxicity besides other physiological and molecular defense responses like decrease in growth rate, chlorophyll content and photosynthesis efficiency, intensification of antioxidative mechanisms, regulation of transcription factors, trace elements chelation, and sequestration into vacuole via trace elements transporters. The sole differentially expressed ATP-binding cassette (ABC) transporters indicated that ABC transporters might play a very important role in the transport and relocation of Pb in C. reinhardtii. Additionally, our data provide the required knowledge for future investigations regarding Pb toxicity and defense mechanisms in algae, and detection of trace elements pollution in environment.